2020
DOI: 10.1007/s10439-020-02642-6
|View full text |Cite
|
Sign up to set email alerts
|

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods

Abstract: To further the understanding of long-term sequelae as a result of repetitive head impacts in sports, in vivo head impact exposure data are critical to expand on existing evidence from animal model and laboratory studies. Recent technological advances have enabled the development of head impact sensors to estimate the head impact exposure of human subjects in vivo. Previous research has identified the limitations of filtering algorithms to process sensor data. In addition, observer and/or video confirmation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…With regard to head impacts, placement of the wearable sensors may be challenging, as they are prone to be broken by the impact. Wearable sensors for assessments of head impacts are available in several systems; they are embedded in instrumented helmets, headbands, mouthguards, and skin patches [ 89 , 90 ]. Of the ten studies included in the data material, skin patches (xPatch) were used in four studies [ 36 , 41 , 54 , 58 ], instrumented helmets (GForce Tracker and SpeedFlex/HIT) were used in five studies [ 36 , 40 , 42 , 45 , 51 ], a headband (SIM-G) was used in one study [ 48 ], and finally MVTrak, with a sensor placed in the ear canal, was used in one study [ 53 ] (number summarizes to eleven, as the study by Cortes et al [ 36 ] utilized xPatch for females and GForce Tracker for males).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to head impacts, placement of the wearable sensors may be challenging, as they are prone to be broken by the impact. Wearable sensors for assessments of head impacts are available in several systems; they are embedded in instrumented helmets, headbands, mouthguards, and skin patches [ 89 , 90 ]. Of the ten studies included in the data material, skin patches (xPatch) were used in four studies [ 36 , 41 , 54 , 58 ], instrumented helmets (GForce Tracker and SpeedFlex/HIT) were used in five studies [ 36 , 40 , 42 , 45 , 51 ], a headband (SIM-G) was used in one study [ 48 ], and finally MVTrak, with a sensor placed in the ear canal, was used in one study [ 53 ] (number summarizes to eleven, as the study by Cortes et al [ 36 ] utilized xPatch for females and GForce Tracker for males).…”
Section: Discussionmentioning
confidence: 99%
“…Linear and rotational acceleration magnitudes from lab studies have been shown to be over-predicted for sensor solutions in both skin patches and instrumented helmets [ 92 ]. False positive high acceleration impacts have further been revealed in field studies, and the importance of video confirmation of sensor-recorded events to remove false positives is in a recent systematic review by Patton et al emphasized to avoid overestimation of head impact exposure [ 90 ]. Still, two-thirds of the included studies in their review did not include video.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various technology has been introduced to assist in the identification of head impacts and suspected concussions during athlete competitions. For instance, sideline video review [9,10], and to a lesser extent, impact sensors in helmeted and non-helmeted sports have been introduced to measure kinematic forces to the head [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…22 This is especially concerning since head impact sensor data is often taken at face value without using video to verify that all recorded impacts were true positives. 20 To provide an objective evaluation of both laboratory and on-field performance of head impact sensors, Kieffer et al developed a twophase approach to sensor testing. 13 The first phase used a pendulum impactor to test laboratory performance, followed by the second phase of on-field testing from video verification of impacts if the sensor performed adequately in the laboratory.…”
mentioning
confidence: 99%